I am legend [videorecording (DVD)] - Lawrence, Francis; Smith, Will, 1968-; Braga, Alice; Tahan, Charlie; Matheson, Richard, 1926-2013; Corrington, John William; Corrington, Joyce H. (Warner Home Video, 2007)
Robert Neville is the last human survivor in what is left of New York City. A pandemic has left only 1% of the population alive and most of those who survived are no longer human. The infected, now lurking in the shadows, watch Neville's every move. Perhaps mankind's last, best hope, Neville is driven by the only one remaining mission: to find a way to reverse the effects of the virus using his own immune blood.